Does the Human Right to Healthcare Apply Universally? A Contribution from a Trauma Therapeutic Perspective - Hanewald, Bernd; Berthold, Daniel; Stingl, Markus; Justus Liebig University Giessen (My University, 2023)
Access to the best possible healthcare is a fundamental human right. However, the provision of medical treatment is not only dependent on the actual treatment options available and the type of illness to be treated but is significantly influenced and restricted by structural and legal conditions. This is particularly evident in the case of refugees and other groups such as the so-called “paperless”, whose access to medical treatment is de facto seriously impeded or denied altogether. At the same time, these individuals are particularly vulnerable to the development of mental illness for a variety of reasons. Refugees in particular often suffer from trauma sequelae, resulting in a broad range of impairments. Based on a case study of a refugee woman living in her host country, the interactions between mental illness and limited psychiatric/psychotherapeutic treatment options due to legal restrictions are analyzed from a medical perspective. Her initially only medically oriented treatment was insufficient to mitigate the consequences of these restrictions. As it was a protracted treatment process, the legal aspects of her case therefore also had to be decisively considered. This case study shows that the human right to the best possible healthcare can be considerably restricted by structural requirements, which, in the case of sequential traumatization and severe illnesses with suicidal tendencies, can be labelled as structural violence.
Keywords: post-traumatic stress disorder; trauma sequelae; flight; structural violence; human rights; ddc:610